Seeing differently: A history and theory of identification and the visual arts - Jones, Amelia (Routledge, 2012)
Voir différemment propose une histoire et une théorie des idées sur l'identité en relation avec les discours et les pratiques des arts visuels dans la culture euro-américaine, depuis les premières croyances modernes selon lesquelles l'art est l'expression d'un individu, l'image peinte une « image du monde » exprimant une vision globale et point de vue cohérent, à la montée des politiques identitaires après la Seconde Guerre mondiale dans le monde de l'art et au-delà. Le livre est à la fois une histoire de ces idées (par exemple, retraçant la domination d'un modèle binaire de soi et de l'autre de Hegel à travers la politique identitaire classique des années 1970) et une réponse politique à la revendication commune dans l'art et le discours politique populaire que nous sommes " au-delà » ou « post- » identité. En contestant cette dernière affirmation, Seeing Differently examine de manière critique comment et pourquoi nous « identifions » les œuvres d'art avec une subjectivité expressive, notant l'impossibilité de prétendre que nous sommes une « post-identité » étant donné la persistance des croyances dans le discours artistique et la culture visuelle plus large sur qui « est » le sujet et propose une nouvelle théorie sur la manière de penser ce type d'identification de manière plus réfléchie et autoréflexive. En fin de compte, Seeing Differently propose un mode de pensée de l'identification en tant que processus de « durée féministe queer » qui ne peut jamais être entièrement résolu, mais doit être pris en compte dans la réflexion sur l'art et la culture visuelle. La duréenalité féministe queer est un mode d'interprétation relationnelle qui affecte à la fois «l'art» et «l'interprète», nous rendant potentiellement plus conscients de la façon dont nous évaluons et valorisons l'art et d'autres types de culture visuelle.
Keywords: LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cinéma; communication; cours; discipline; fem1000; genre; har4600; identités LGBTQIA2+; médias; premier cycle; queer; thématiques

The feminism and visual culture reader - Jones, Amelia (Routledge, 2010)
Feminism is one of the most important perspectives from which visual culture has been theorized and historicized over the past forty years. Challenging the notion of feminism as a unified discourse, this second edition of The Feminism and Visual Culture Reader assembles a wide array of writings that address art, film, architecture, popular culture, new media and other visual fields from a feminist perspective. The essays, 40% of which are new to the second edition, are informed by the authors’ deep attention to historical, geographical, and disciplinary contexts as well as by cutting edge concerns such as globalization, diasporic cultural shifts, developments in new media technologies, and intersectional identity politics. The Feminism and Visual Culture Reader combines classic texts with six specially commissioned pieces, all by leading feminist critics, historians, theorists, artists, and activists. Articles are grouped into thematic sections, each of which is introduced by the editor. Providing a framework within which to understand the shifts in feminist thinking in visual studies, as well as an overview of major feminist theories of the visual, this reader also explores how issues of race, class, nationality, and sexuality enter into debates about feminism in the field of the visual
Keywords: 1900-1999; LGBTQIA2+; approches et analyses; arts visuels et médiatiques; cours; discipline; discours dominant; fem1000; genre; har4600; identités LGBTQIA2+; interdisciplinarité; intersectionnalité; premier cycle; périodes historiques; racialisation; sexualité; systèmes d'oppressions; thématiques; théories féministes; études culturelles

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."--Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Le corps de l'artiste - Warr, Tracey; Jones, Amelia; Warr, Tracey; Jones, Amelia (Phaidon, 2005)
Au cours du XXe siècle, de nombreux artistes ont utilisé leur corps à la fois comme sujet et comme objet de leur oeuvre. Le corps est présenté dans tous les états possibles et l'artiste vit littéralement son art que ce soit dans le cadre de performances, ou dans l'intimité, avec la photographie et la vidéo. Ouvrage conçu par T. Warr.
Keywords: 1900-1999; arts; corps; cours; discipline; har4600; histoire de l'art; premier cycle; périodes historiques; thématiques

Otherwise: imagining queer feminist art histories - Jones, Amelia; Silver, Erin (Rethinking art's histories, 2016)
Otherwise: Imagining queer feminist art histories" is the first publication to address queer feminist politics, methods and theories in relation to the visual arts, including new media, installation and performance art. Despite the crucial contribution of considerations of 'queer' to feminism in other disciplines of the humanities, and the strong impact of feminist art history on queer visual theory, a visible and influential queer feminist art history has remained elusive. This book fills the gap by offering a range of essays by key North American and European scholars, both emerging and renowned, who address the historiographic and political questions arising from the relationship between art history and queer theory in order to help map exclusions and to offer models of a new queer feminist art historical or curatorial approach.
Keywords: LGBTQIA2+; amérique du nord; amériques; approches et analyses; art contemporain; arts; arts visuels et médiatiques; cours; discipline; europe; har4600; histoire de l'art; identités LGBTQIA2+; installation; performance; premier cycle; queer; régions géographiques; thématiques; transféminisme